Rekonstruksi Identitas Gender dalam Masyarakat Multikultural - Anastasya Sembiring; Sri Yunita; Debora Matanari; Putriani Sinaga; Yakinda Munthe (Universitas 17 Agustus 1945 Semarang, 2024)
Multicultural is often used to describe the unity of various ethnic groups in a country. This journal explains what gender equality looks like from a multicultural perspective. This research is a literature review. When discussing equality, the focus is on the fair treatment of all people. Differences are part of true equality, and groups must have special rights to compensate for existing differences. When analyzing the basic assumptions of the principle of equality and recognition of differences, several problems were discovered. First, there is tension between one group and another, where multiculturalism ironically emphasizes differences between cultural groups and ignores similarities. Second, conflicts may arise between minority groups who demand equal rights. If we want to further advance our multicultural agenda, we need to address these issues.